Diverse thioether macrocyclized peptides through a radical SAM maturase - Karsten A. S. Eastman; Andrew G. Roberts; Vahe Bandarian (Proceedings of the National Academy of Sciences, 2025)
Disulfide bonds stabilize many bioactive peptides, but their susceptibility to reduction under physiological conditions limits broad applicability in biotechnology. PapB is a promiscuous radical S -adenosyl-L-methionine enzyme that is involved in the maturation of PapA, which is a ribosomally produced and posttranslationally modified polypeptide. PapB introduces six thioether linkages between internal Cys residues and carbon atom that is α to the side-chain carboxylate of Asp/Glu residues C-terminal to the Cys residues. Herein, we show that PapB also efficiently couples an internal Cys thiol to the C-terminal carboxylate of peptides terminating in D- or β-amino acids, forming α- or β-thioether macrocycles. Moreover, PapB tolerates β- and N-methyl amino acids within the peptide, resulting in the formation of macrocycles that are comprised entirely of unnatural amino acids, such as peptides containing all β-residues. These findings establish PapB as a sequence-agnostic thioether ligase for efficient C-terminal macrocyclization. Our work expands the enzymatic toolbox for constructing conformationally constrained peptides for therapeutics and chemical biology.